(untitled) (Journal of Tourism & Adventure, 2022)
Tourism has gradually developed in the wave of human civilization. However, it has not reached the level of Sustainable Tourism Development (STD). This paper is trying to explore its underneath causes by applying the desk study research method. This study has underscored two major reasons for no confirmation of STD to date. The first one is the misuse of Local Community Participation (LCP) instead of assuring the sovereign role of locals for their participation from tourism planning to its execution. The second one is ‘no successful attempts of the researchers to make holistic planning from different approaches given by the researchers in the ‘tourism and travel’. Furthermore, in the developing economy where good governance is hard to realize, even the sectoral planning of each economic sector is to be made and implemented as a backup plan.